Food Consumption Frequency, Perceived Stress, and Depressive Symptoms Among Female University Students in Dubai, United Arab Emirates - Mohamad, Ohoud; Al Sabbah, Haleama; Smail, Linda; Hermena, Ehab W.; Al Ghali, Rola (Frontiers in Sustainable Food Systems, 2022)
Background This study assessed whether perceived stress and depressive symptoms were associated with the frequency of consumption of specific food groups among female university students. Methods A cross-sectional study was conducted among female university students using a simple random sampling method. The response rate was 97%, with a total number of 385 participants. The associations between stress levels and most/least-consumed food groups, and between depressive symptoms levels and most/least-consumed food groups were assessed. The questionnaire included a 12-item self-administered food frequency questionnaire, Cohen's Perceived Stress Scale, and the Beck Depression Inventory-II. The study was approved by the University Ethical Committee prior to the data collection. One-way Analysis of Variance (ANOVA) and an independent-sample t-test were performed to test the equality of population means across the categories of each independent variable depending on the number of categories of the independent variable. Results Overall, this group of female university students fell under the mild mood disturbance category (depressive symptoms) (BDI-II) and had moderate perceived stress (PSS). Perceived stress was associated with more frequent consumption of salad/raw vegetables and cooked vegetables and less frequent consumption of cake/cookies and meat/sausage products (p < 0.05). Additionally, depressive symptoms were associated with less frequent consumption of fresh fruits and increased consumption of fast food/canned food and soft drinks (p < 0.05). Conclusions The data showed that stress and depression were associated with different dietary preferences, which is consistent with the distinctions between stress and depression in human behavior. Specifically, the results revealed associations between soft drinks consumption and higher depressive symptoms and between frequent consumption of salad/raw vegetables and cooked vegetables and higher perceived stress among this group of female university students.